Professional awareness among Riyadh teachers government and private (Comparative Study) (Journal of the College of Education for Women, 2019)
Take the teacher's key position in the educational system as a foundation stone and primarily responsible for achieving the goals of Education , and efficient teacher conscious is the teacher who prepared educationally and specialized training well add to the enjoyment of a range of features that enable them to adjust and compatibility with educational developmentsHence the problem of the study questioning the Kindergarten Does teacher professional awareness that enable it to perform its work learned from experienceThe research sought to measure1-Professional awareness among teacher Kindergarten2-Professional awareness of Kindergarten parameters depending on the type of kindergarten.Limited search parameters Riyadh government and private academic year ( 2013- 2014 )In order to achieve the objectives of the research , the researcher built a standard professional awareness and enough mental according to the steps of scientific building psychometric After drafting paragraphs scale professional awareness and number (50) paragraph , it was ascertained the veracity of the scale -mediated presentation to a group of experts , has proven its validity after making some adjustments bringing the number of paragraphs (34) items , as well as a researcher statistical analysis of the vertebrae in with your strength discriminatory , and the researcher delete (8) paragraphs of scale professional awareness of the lack of distinguishable The rest of the paragraphs were found to be distinct and statistically significant , as well as the creation of a relationship degree paragraph primarily college, was sure of the stability of the scale in a way re-testing , with a reliability coefficient ( 0.83 ), and this shows that the reliability coefficient good . Increase the application of the equation of Alpha Kronbak , and found that the reliability coefficient equal to ( 0.89 ) and this shows good stabilityScales were applied to a sample numbered ( 300 ) parameter of the kindergarten teachers of government and private , were chosen the way of simple random , research has come to the following conclusions :1-Enjoys kindergarten teachers in the city of Baghdad, a professional high- consciously.2-There are no statistically significant differences between the Riyadh government and private variable in professional awareness.